Optimizing Energy Consumption for Cloud Internet of Things - Ahmed, Zeinab E.; Hasan, Mohammad Kamrul; Saeed, Rashid A.; Hassan, Rosilah; Islam, Shayla; Mokhtar, Rania A.; Khan, Sheroz; Akhtaruzzaman, Md (Frontiers in Physics, 2020)
The Internet of Things (IoT) and Cloud Computing are considered to be two of the greatest technology revolutions in the last few years. New technology raised in recent years is known as Cloud IoT or the Cloud of Things (CoT), which integrates cloud computing and the Internet of things. Dynamic and heterogeneous environments, energy efficiency, and delay-sensitivity are the major issues with the CoT. Energy efficiency is one of the basic requirements of IoT applications and resources in the cloud, which is a challenging issue in the CoT. This paper proposes the optimization of energy schemes for the CoT by applying a Genetic Algorithm (GA). Extensive numerical simulation is carried out to verify the effectiveness of the proposed method compared to the ETCORA algorithm. The analytical results present better performances of the proposed optimizing energy consumption technique. Results also show that the proposed method indeed outperforms the ETCORA in reducing the energy consumption of task requests.